Cover Picture: Tunable Properties of Functional Nanoparticles for Efficient Capture of VOCs (ChemistrySelect 31/2017). Issue 31 (2nd November 2017) - Guerra, Fernanda D.; Campbell, McKenzie L.; Whitehead, Daniel C.; Alexis, Frank
Abstract : The cover picture shows gaseous capture of volatile organic compounds (VOCs) using polyethylenimine functionalized biodegradable nanoparticles. Major sources of VOCs include industrial facilities, motor vehicle exhaust, electric utilities, gasoline vapors, and chemical solvents. Furthermore, many industrial processes are affected by nuisance odors caused by the release of VOCs to the air. Therefore, poly(D, L‐lactic acid)‐polyethylenimine (PDLA‐PEI) nanoparticles could be employed as an alternative material for remediation of VOCs. More information can be found in the Full Paper by Alexis and Whitehead et al . (DOI:10.1002/slct.201701736 )